Spectrum of cardiovascular diseases in six main referral hospitals of Ethiopia. Issue 2 (19th June 2017) - Yadeta, Dejuma; Guteta, Senbeta; Alemayehu, Bekele; Mekonnen, Dufera; Gedlu, Etsegenet; Benti, Henock; Tesfaye, Hagazi; Berhane, Samuel; Hailu, Abraha; Luel, Abadi; Hailu, Tedros; Daniel, Wandimu; et al.
Abstract : Background: The spectrum of cardiovascular diseases varies between and within countries, depending on the stage of epidemiological transition and risk factor profiles. Understanding this spectrum requires regional and national data for each region or country. This study was designed to determine the spectrum of cardiovascular diseases in six university hospitals in Ethiopia. Methods: This is a cross-sectional study of the spectrum of cardiovascular diseases in six main referral/teaching hospitals located in different parts of the country. Consecutive patients visiting the follow-up cardiac clinics of these hospitals from 1 January to 30 June 2015 were included in the study. Data were collected on a pretested questionnaire. Results: A total of 6275 patients (58.5% females) were included in the study. Nearly 61% of the patients were from urban areas. The median age was 33 years (IQR 14–55 years). Valvular heart disease was the most common diagnosis, accounting for 40.5% of the cases. Of 2541 patents with valvular heart disease, 2184 (86%) were cases of chronic rheumatic heart disease. Conclusion: Our study shows that chronic rheumatic valvular heart disease is the most common cardiovascular diagnosis among patients seen at cardiology clinics of six referral/teaching hospitals in the country, followed by congenital heart diseases. Hypertensive and ischaemic heart diseases also accounted for a significant proportion of the cases. Therefore, strategies directed towards primary and secondary prevention of acute rheumatic fever as well as prevention of risk factors for hypertension and ischaemic heart disease may need to be strengthened.